Legal Implications of Inaccurate Petitum in Land Registration (Study of Donggala District Court Decision Number: 7/PDT.G/2020/PN.DGL) - Septiana Dewi, Eka; Santoso, Bambang; Mulyanto, Mulyanto (Universitas Islam Sultan Agung, 2025)
Land registration is mandated by law to provide legal certainty. Likewise, Registration is mandatory for the transfer of land ownership rights resulting from a sale and purchase agreement since the enactment of the UUPA; Customary law historically governed land sales and purchases, and it serves as the foundation for the national agrarian law system, namely the existence of precise, cash, and actual conditions. The consequence of not fulfilling the precise conditions in the Donggala District Court Decision No: 7 / Pdt.G / 2020 / PN.Dgl is that buyers have difficulty registering their land rights to obtain proof of rights through a certificate of ownership. However, the state has provided legal protection for land registration based on court decisions. Buyers who obtain land rights in good faith obtain repressive legal protection by filing a lawsuit with the court. However, not all court decisions can be executed. The decision in Donggala District Court Case No: 7/Pdt.G/2020/PN.Dgl resulted from the plaintiff's petitum omitting both a request for a ownership certificate to be issued in the plaintiff's name and the inclusion of the Head of the local Land Office as a party to the case. This is a normative legal study that analyzes legal materials using the syllogistic deduction method. This study aims to determine whether the Donggala District Court Decision Number: 7/Pdt.G/2020/PN.Dgl can be used legally for the plaintiff's land registration. The study results indicate that because the judge's ruling is confined to the relief sought in the plaintiff's petitum, no order was issued to the Head of the local Land Office to issue a certificate of ownership in favor of the plaintiff. Thus, the Donggala District Court Decision No: 7/Pdt.G/2020/PN.Dgl is difficult to implement as a basis for plaintiff's land registration.